2015
DOI: 10.1016/j.rmed.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Complex interventions reduce use of urgent healthcare in adults with asthma: Systematic review with meta-regression

Abstract: Complex interventions reduced the use of urgent healthcare in adults with asthma by 21%. Those complex interventions including skills training, education and relapse prevention may be particularly effective in reducing the use of urgent healthcare in adults with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Meta-regression can be used for this, using covariates to code the presence of particular features in each intervention implementation. As an example, Blakemore et al analysed 39 intervention comparisons from 33 independent studies aiming to reduce urgent healthcare use in adults with asthma 52. Effect size estimates were coded according to components used in the interventions, and the authors found that multicomponent interventions including skills training, education and relapse prevention appeared particularly effective.…”
Section: Synthesis Methods For Understanding Components Of the Intervmentioning
confidence: 99%
“…Meta-regression can be used for this, using covariates to code the presence of particular features in each intervention implementation. As an example, Blakemore et al analysed 39 intervention comparisons from 33 independent studies aiming to reduce urgent healthcare use in adults with asthma 52. Effect size estimates were coded according to components used in the interventions, and the authors found that multicomponent interventions including skills training, education and relapse prevention appeared particularly effective.…”
Section: Synthesis Methods For Understanding Components Of the Intervmentioning
confidence: 99%
“…Meta‐regression for core component analysis—or “unpacking the black box” as some call it (Solmeyer & Constance, 2015)—is widely used across many policy areas, including health (Filene et al, 2013), prevention services (Wilson et al, 2020), education (Farrington & Ttofi, 2009), and workforce development (Bloom et al, 2003). Blakemore and others (2014) used meta‐regression as part of their examination of core components in a broad range of interventions for people with asthma in order to identify the characteristics that were associated with a reduction in the use of urgent health care. The interventions were grouped according to program approaches and coded for general and specific core components, study design features, target group characteristics, and contextual conditions, among other aspects.…”
Section: The Three Waves Of Evidence Reviewsmentioning
confidence: 99%
“…One of the reviews focused on asthma 112 and the other on COPD. 111 The similarity of the results from these two reviews (> 60 studies), coupled with published data on other LTCs, 320,[365][366][367] suggests that psychosocial interventions may have similar effects in LTCs, regardless of the individual nature of the condition itself.…”
Section: Long-term Conditions and Multimorbiditymentioning
confidence: 99%
“…111,112,333,365,366 Treatment of psychosocial problems may provide an added dimension to the overall care of people with LTCs, which has been relatively neglected to date.…”
Section: Reasons Why People With Long-term Conditions Use Unscheduledmentioning
confidence: 99%